Assessment of Students Satisfaction with Online Learning Experiences during the COVID-19 Pandemic: Customer Satisfaction Index and Importance Performance Analysis: Case Study at Institut Teknologi Kalimantan - Noni Oktiana Setiowati; Abdul Alimul Karim; Eka Krisna Santoso (SPECTA Journal of Technology, 2022)
As COVID-19 has became a pandemic, all universities have been switched their learning methods into online classes. This new learning method certainly affects the conventional learning students, including two of six effective learning indicators according to Directorate General of Higher Education are no longer directly related to university namely students’ activities/behaviour and learning climate. This research aims to measure the student satisfaction with online learning experiences during the COVID-19 pandemic at Institut Teknologi Kalimantan (ITK) using Customer Satisfaction Index (CSI) based on those six indicators. Importance Performance Analysis (IPA) was used to determine the most important attributes which affected the measured satisfaction or dissatisfaction. The results of this study shows that students at ITK have satisfaction level of 74.79 % who fall into the Satisfied category, this number shows that the implementation of online lectures at ITK had met students’ expectations. The result of attribute mapping using IPA method shows that the students’ disatisfaction mostly come from one item at learning climate indicator that stated about studying comfortably and conducively at home, it means that the students cannot concentrate when taking online lectures at home. Fortunately, the rest of important attributes had met students’ expectations. Keywords: COVID-19, Student satisfaction, CSI, IPA, ITK, Online lectures, Learning climate